2011
DOI: 10.3141/2205-19
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Skid Resistance Measurement for Porous Asphalt Pavement Management

Abstract: This paper focuses on developing a method for road managers to assess the sideways-force coefficient (SFC) in porous asphalt with low-cost standard tests. SFC can be used as a component in road surface condition surveys and asset management decisions. A standard piece of equipment for determining SFC is the sideways-force coefficient routine investigation machine (SCRIM), which can be truck or trailer mounted. This equipment is often beyond the budget of most small, low-volume road agencies. An empirical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…It should be noted that the desired thickness of adhesive material applied at the interface was achieved by controlling the mass of adhesive material after knowing the density and coating area. The density of polyurethane, epoxy resin, and SBS modified asphalt is 1.003 g/cm 3 , 0.971 g/cm 3 and 1.030 g/cm 3 , respectively.…”
Section: Experimental Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the desired thickness of adhesive material applied at the interface was achieved by controlling the mass of adhesive material after knowing the density and coating area. The density of polyurethane, epoxy resin, and SBS modified asphalt is 1.003 g/cm 3 , 0.971 g/cm 3 and 1.030 g/cm 3 , respectively.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…With the high air void content (18%-22%), OGFC offers safety advantages in terms of high skid resistance and no splash or spray in addition to its benefits in noise reduction and water runoff quality enhancement [3][4][5][6]. Despite of the functionality benefits of OGFC, engineering practices have found that the application of OGFC faces three challenges during the service life of pavement, including clogging of air voids [7,8], raveling [9][10][11], and freezing-induced damage in winter [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, developed countries have road surface problems resulting from work zones, climatic conditions, and excessive loads etc. In order to detect and fix these mentioned problems, many countries have been working to monitor these deformations by utilizing special devices and techniques (TRB 2004;Oloufa et al 2004;Lee, Kim 2005;Battiato et al 2006;Dell' Acqua et al 2011;Strazdins et al 2011;Žilionienė et al 2013). Downloaded by [University of Sussex Library] at 14:26 28 June 2016…”
Section: Introducionmentioning
confidence: 99%
“…See also Dell'Acqua et al (2011b, 2012a. The parameter used in this study to assess the characteristics of the upper layer of the runway pavement, in order to evaluate its safety and function ability by De , is friction.…”
Section: Introductionmentioning
confidence: 99%